If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7(6 + -4P) + 2P = 0 (6 * 7 + -4P * 7) + 2P = 0 (42 + -28P) + 2P = 0 Combine like terms: -28P + 2P = -26P 42 + -26P = 0 Solving 42 + -26P = 0 Solving for variable 'P'. Move all terms containing P to the left, all other terms to the right. Add '-42' to each side of the equation. 42 + -42 + -26P = 0 + -42 Combine like terms: 42 + -42 = 0 0 + -26P = 0 + -42 -26P = 0 + -42 Combine like terms: 0 + -42 = -42 -26P = -42 Divide each side by '-26'. P = 1.615384615 Simplifying P = 1.615384615
| -(n-3)+7(3+n)-2n+7n= | | 3(7q+6)=3q | | 3-4k=11 | | -8(1m-6)=88 | | -13m=-3777 | | 2.4(m-3)+8=-8.2 | | 58=2thirdw | | -4(-5n-4)=-144 | | 7(4+3x)=196+3x | | -x+3=40 | | (2x+1)+(3x-3)+(9x)=180 | | 5x-2d+1=15 | | 2=-11k | | A=1020(1-0.195)15 | | -x-3=16 | | 29x+160=73 | | y=0.23x+27 | | 10x+260-5x=450 | | A=1020(1-0.0195)20 | | 16x+14=39 | | x^2-6+34=0 | | 4p+7=3+4+4p | | -6x^2+5x-(6x^2-5x+6)= | | 13-16=3y+6-2y | | 7y+7=9+2y+2y | | n-(6.12)=-1.3 | | 7x+2(5+2x)=87 | | -19+17= | | 14x-1-13x-1=-3 | | 3h^2+6h+6=0 | | 2(4z-5-3)=166-46 | | -10c-4=-6+5c |